The food lover's healthy habits cookbook - Helm, Janet (Dietitian) (Oxmoor House, 2012)
Collects the twelve healthy habits program from Cooking Light magazine that replaces old habits with new behaviors, from eating breakfast and exercising to eating mindfully and being aware of portion-size.